Kriteria Penggunaan Sistem Pendukung Keputusan Pada SMK Negeri Di Kota Malang - Devita Maulina (Faculty of Computer Science, University of Jember, 2017)
The development of the world of technology is currently growing very fast over time. This development is expected to be useful for humans in their survival. Currently in vocational schools are often encountered various kinds of problems. To solve the problem done unilaterally by the leadership or any particular party. The problem in SMK Negeri in Malang city is very much and the decision is more likely to be taken by the principal and is unilateral. DSS is a decision support system that can be an application or others by utilizing technological developments. Kinds of SPK there are several methods that are often used are AHP, SAW, TOPSIS, Fuzzy, etc .. The use of SPK for problem solving in SMK is required appropriate support criteria for the results to be valid. This writing produces what criteria are needed in Decision Support System to overcome various problems that often occur in SMK.